Micropropagation of a Valuable Ethnomedicinal Plant Streblus asper Lour. - Kota, V.R. Kokkirala, K. Kasula, S. Abbagani*, K. Gadidasu, P. Umate, M. Aileni, S.R. (Journal of Phytology, 2011)
A micropropagation protocol is presented for conservation of critically threatened woody tree species, Streblus asper Lour. In vitro axillary bud proliferation followed by multiple shoot induction was obtained using mature nodal segments. Initially, explants were cultured on Murashige and Skoog’s medium supplemented with different concentrations of BA (2.2, 4.4, 6.6, 8.9, 11.1 and 13.3 µM), Kn (2.3, 4.6, 6.9, 9.3, 11.6 and 13.9 µM) or TDZ (2.2, 4.5, 6.7, 8.90, 11.1 and 13.5 µM). These individual levels of cytokinins did not support in vitro shoot regeneration in S. asper. Combinations of cytokinins, Kn with BA or TDZ, significantly influenced shoot regeneration ability. The combination of Kn (4.60 µM) with BA (4.44 µM) evoked an optimum response towards shoot proliferation whereas, medium containing Kn (4.60 µM) plus TDZ (4.54 µM) induced multiple shoot formation. In vitro developed microshoots were rooted on MS half strength medium supplemented with 2.46 µM IBA. The plantlets established in vitro were transferred to pots containing sterilized soil and vermiculite (1:1) mixture and were hardened in the greenhouse with 70-75% survival rate. Key words: Clonal propagation, Cytokinins, Mature nodal explant, Medicinal woody tree, Multiple shoot induction Abbreviations: BA - 6-benzyladenine, IBA - indole 3-butyric acid, Kn - kinetin, µM - micro moles, MS – Murashige and Skoog TDZ - thidiazuron <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Kranthi Gadidasu et al. Micropropagation of a Valuable Ethnomedicinal Plant Streblus asper Lour.. J Phytol 3/2 (2011) 18-23